Financial toxicity and acute injury in the Kilimanjaro region: An application of the Three Delays Model. - Parker Frankiewicz; Yvonne Sawe; Francis Sakita; Blandina T Mmbaga; Catherine Staton; Anjni P Joiner; Emily R Smith (PLoS ONE)
Background Trauma and injury present a significant global burden-one that is exacerbated in low- and middle-income settings like Tanzania. Our study aimed to describe the landscape of acute injury care and financial toxicity in the Kilimanjaro region by leveraging the Three Delays Model. Methods This cross-sectional study used an ongoing injury registry and financial questionnaires collected at Kilimanjaro Christian Medical Centre (KCMC) in Moshi, Tanzania from December 2022 until March 2023. Financial toxicity measures included catastrophic expenditure and impoverishment, in accordance with World Health Organization standards. Descriptive analysis was also performed. Findings Most acute injury patients that presented to the KCMC Emergency Department experienced financial toxicity due to their out-of-pocket (OOP) hospital expenses (catastrophic health expenditure, CHE: 62.8%; impoverishment, IMP: 85.9%). Households within our same which experienced financial toxicity had more dependents (CHE: 18.4%; IMP: 17.9% with ≥6 dependents) and lower median monthly adult-equivalent incomes (CHE: 2.53 times smaller than non-CHE; IMP: 4.27 times smaller than non-IMP). Individuals experiencing financial toxicity also underwent more facility transfers with a higher surgical burden. Interpretation Delay 1 (decision to seek care) and Delay 2 (reaching appropriate care facility) could be significant factors for those who will experience financial toxicity. In the Tanzanian healthcare system where national health insurance is present, systematic expansions are indicated to target those who are at higher risk for financial toxicity including those who live in rural areas, experience unemployment, and have many dependents.